ASPECTS OF APPLICATION OF TRANSACTION ANALYSIS - Denshchikov V. K., Lykova O. A. (Scientific studies and modern education, 2019)
this article presents the most popular aspects of transaction analysis. This analysis provides a solution to the problems associated with complex situations in the dialogue in the client business
Keywords: Personality; analysis; behavior; client; person; ego States; трансактный анализ; эго-состояние; принципы трансактного анализа